Using the concrete representational abstract (CRA) instructional framework for mathematics with students with emotional and behavioral disorders. Issue 2 (3rd April 2018) - Peltier, Corey; Vannest, Kimberly J.
ABSTRACT: Mr. Buxton is a perplexed elementary mathematics teacher. He co-teaches a second-grade classroom, with Ms. Snyder. In their classroom they have 25 students; five are identified as academically at risk, and three receive special education services. In the past Mr. Buxton successfully used an instructional approach consisting of (a) modeling, (b) guided practice, (c) independent practice, and (d) formative assessment. Currently, students are struggling to subtract two- and three-digit numbers requiring regrouping. The co-teacher, Ms. Snyder, suggests that the students need more visuals and concrete examples during instruction. Mrs. Zampelli teaches third grade in a general education classroom. She has support from the special education teacher and a paraeducator who provide consultation and instructional coaching. Of the 18 students in her class, nine have Individual Education Programs. The special education teacher, Mr. Ortiz, provides great suggestions to make learning "hands-on." However, the concept of fractions and specifically comparing fractions with like numerators or denominators causes problems every year. Both teachers emphasize multiple representations (e.g., fraction cubes, fraction circles, fraction bars, number lines) of the concepts. Students are able to solve problems when working with manipulatives but struggle to solve problems in the abstract. Leading teammates suggest a more structured framework for incorporating manipulatives and representations.